Session Topic: Recent Studies of Financial Markets and Institutions: Discussion - Blume, Marshall E.; Lindsay, Robert; Shapiro, Eli; Stigler, George J. (Journal of Finance, 1972)
Marshall E. Blume, Robert Lindsay, Eli Shapiro, George J. Stigler, Session Topic: Recent Studies of Financial Markets and Institutions: Discussion, The Journal of Finance, Vol. 27, No. 2, Papers and Proceedings of the Thirtieth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 27-29, 1971 (May, 1972), pp. 329-341